MOLECULAR DESIGN OF N-ACYL DERIVATIVES OF 2-(2-OXOPYROLIDIN-1-YL)-ACETAMIDE WITH GABA-ERGIC AND GLUTAMATERGIC ACTIVITIES - I. P. Kodonidi; A. S. Chiriapkin; D. E. Tworowski (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The first of the most successfully implemented nootropic drugs in medical practice is piracetam, which should be attributed to cyclic derivatives of gamma-aminobutyric acid. The production of new piracetam derivatives with high nootropic activity is a promising direction in the development of new neuroprotective drugs.The aim of the study is to predict GABA-ergic and glutamatergic activities of N-acyl derivatives of 2-(2-oxopyrolidin-1-yl)- acetamide by a molecular docking method through the energy analysis of interaction of modeled structures with GABAA and AMPA receptors with their subsequent targeted synthesis.Materials and methods. The objects of the research are new N-acyl derivatives of 2-oxo-1-pyrrolidineacetamide and a virtual model of the GABAA receptor of the Homo sapiens organism with the identification code 6D6U and a three-dimensional model of the AMPA-receptor of the Rattus norvegicus organism with the identification code 3LSF from the RCSB PDB database. The simulated compounds were designed in the HyperChem 8.0.8 program. This program was also used to optimize geometry using the force field of molecular mechanics MM+. Molecular docking was carried out using the Molegro Virtual Docker 6.0.1 program. The preparation of N-acyl derivatives of 2-(2-oxopyrrolidin-1-yl)-acetamide was carried out by the interaction of 2-(2-oxopyrrolidin-1-yl)-acetamide with an excess of the corresponding anhydride under conditions of acid catalysis.Results. Based on the results of molecular docking, a high affinity of all simulated compounds for the binding site of GABAA and AMPA receptors can be estimated. According to the predict, the maximum GABA-ergic activity should be expected for (N-[2-(2-oxopyrrolidin-1-yl)-acetyl]-butyramide. N-acyl derivatives of 2-oxo-1-pyrrolidineacetamide form a more stable complex with amino acid residues Arg207, Phe200, Thr202, Tyr97, Tyr157, Tyr205 and Phe65 of the GABAA receptor binding site than the GABA molecule. In terms of the minimum interaction energy, the N-acyl derivatives of 2-(2-oxopyrrolidin-1-yl)- acetamide are superior to a number of known ligands such as GABA, piracetam, anipiracetam, picamilon and pramiracetam. The tested compounds have also shown a high affinity for the binding site of the AMPA receptor. The leader compound is also the compound PirBut, as in the case of the GABAА receptor.Conclusion. Molecular modeling of the ligands interaction with the active binding site of gamma-aminobutyric acid of the GABAA receptor by molecular docking showed that all virtual N-acyl derivatives of 2-oxo-1-pyrrolidineacetamide can exceed a number of nootropic drugs by activity. In the course of molecular design, a method for predicting a glutamatergic activity for 2-pyrrolidone derivatives has been developed. It suggests a significant nootropic activity for N-[2-(2-oxopyrrolidin-1-yl)- acetamide amides.